BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film and preparation method thereof
By plating a multi-layer film structure on the BaF2 base layer, combining physical vapor deposition and APS ion source-assisted deposition technology, the problems of poor optical performance of the existing BaF2 base anti-reflection film and easy film fall off are solved, and higher film layer firmness and spectral transmittance are achieved, meeting the requirements of the use of the new infrared two-color optical system.
Patent Information
- Application Number
- CN202111280911.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-01
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-11-01
AI Technical Summary
The optical performance of the existing BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film is poor, and the film layer is prone to fall off and cannot meet the use requirements of the new infrared two-color optical system.
The BaF2 base layer is used to sequentially plate multi-layer film structures such as Y2O3, ZnSe, YbF3, ZnSe, Ge, etc., and the thickness and order of each layer are controlled through physical vapor deposition and APS ion source-assisted deposition technology to enhance the density and mechanical strength of the film layer.
It effectively improves the film layer firmness of the anti-reflection film and the spectral transmittance in the 3.7-4.8μm & 7.7-9.5μm band, meeting the environmental and physical firmness requirements in GJB2585-1995 "General Specifications for Optical Film Layers".
Smart Images

Figure CN113866852B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of infrared coating technology, in particular to a BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film and a preparation method thereof. Background Art
[0002] BaF2 is a low-refractive-index material with good optical transmittance in the infrared band and is often used in infrared two-color optical systems. BaF2 material has a certain degree of water solubility, and the film layer of optical parts made of BaF2 material is easy to fall off. It cannot withstand the test of adhesion, humidity, and moderate friction in the GJB2485-1995 "General Specification for Optical Film Layers". In addition, the average transmittance in the dual bands of 3.7-4.8μm and 7.7-9.5μm is not high, which cannot meet the use requirements of the new infrared two-color optical system. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film with poor optical performance, and to provide a BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film and a preparation method thereof.
[0004] The purpose of the present invention is achieved through the following technical solutions:
[0005] A BaF2-based 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film comprises a base layer, on which a Y2O3 layer, a ZnSe layer, a YbF3 layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, and a ZnS layer are sequentially arranged.
[0006] Preferably, the base layer is sequentially provided with a Y2O3 layer with a thickness of 20±5nm, a ZnSe layer with a thickness of 111±2nm, a YbF3 layer with a thickness of 328±3nm, a ZnSe layer with a thickness of 640±5nm, a Ge layer with a thickness of 86±0.5nm, a ZnSe layer with a thickness of 81±1nm, a Ge layer with a thickness of 350±3nm, a ZnSe layer with a thickness of 71±1nm, a Ge layer with a thickness of 147±1.5nm, a ZnSe layer with a thickness of 89±1nm, a YbF3 layer with a thickness of 171±2nm, a ZnSe layer with a thickness of 76±1nm, a Ge layer with a thickness of 72±1nm, a ZnSe layer with a thickness of 36±2nm, a YbF3 layer with a thickness of 585±10nm, and a ZnS layer with a thickness of 130±3nm.
[0007] A method for processing a 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film on a BaF2 substrate, comprising step S2, using physical vapor deposition coating equipment and adopting an APS ion source assisted deposition method to sequentially coat a Y2O3 layer, a ZnSe layer, a YbF3 layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, and a ZnS layer on the surface of a substrate layer.
[0008] Preferably, in step S2, the control parameters in the APS ion source assisted deposition method are: the filling gas is argon, the gas flow rate is 8-10sccm, the bias voltage is 100-120V, the discharge voltage is 60-90V, the discharge current is 20-40A, and the coil current is 1-3A.
[0009] Preferably, in step S2, the plating temperature is 150-170°C.
[0010] Preferably, before step S2, step S1 is further included, wherein step S1 is to bombard the surface of the substrate using an APS ion source of a physical vapor deposition coating device.
[0011] Preferably, in step S1, the control parameters of the APS ion source bombardment are: the filling gas is argon, the gas flow rate is 10-12 sccm, the bias voltage is 100-120 V, the discharge voltage is 60-90 V, the discharge current is 30-50 A, and the coil current is 1-3 A.
[0012] Preferably, in step S1, the bombardment time is 6 minutes.
[0013] Preferably, step S3 is further included after step S2, wherein step S3 is to keep the temperature at the time of deposition for 1 hour after the film layer is deposited and then turn off the heat preservation.
[0014] Preferably, in step S3, the heat preservation is turned off and the parts are cooled to below 50 degrees Celsius before being taken out.
[0015] The present invention can effectively improve the film firmness of the anti-reflection film and the spectral transmittance in the 3.7-4.8μm & 7.7-9.5μm bands. In addition, by plasma bombarding the film layer, the density and mechanical strength of the film layer on the surface of the anti-reflection film are enhanced, and the adhesion and anti-friction ability of the anti-reflection film are improved. Specifically meet the requirements of 3.4.1 film environment and physical firmness in GJB2585-1995 "General Specifications for Optical Film Layers": 1. The film layer is firmly adhered to the surface of the film layer with a 2cm wide tape with a peel strength of not less than 2.74N / cm. After being quickly pulled up vertically, there is no film peeling. 2. Under the conditions of 50℃±2℃ and relative humidity of 95%~100% for 24 hours, the film layer has no defects such as peeling, peeling, cracking, blistering, etc.; the coating surface has no corrosion points, stains, fading, stripes, and suffocation that exceed the spectral performance of the film layer specified in the drawings and relevant technical documents. 3. The film layer was subjected to a pressure of 4.9N. The rubber friction head wrapped with degreased cloth was moved back and forth 50 times (25 times) on the surface of the film layer. The film layer showed no signs of damage such as scratches. In practical applications, it can effectively solve the problem of easy film removal of BaF2 material optical parts. The spectral transmittance index meets the requirements of the new infrared two-color optical system. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic structural diagram of the 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film on a BaF2 substrate of the present invention.
[0017] Figure 2 This is the spectral transmittance curve of the BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film prepared in Example 3.
[0018] Figure 3 This is the spectral reflectivity curve of the 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film on the BaF2 substrate prepared in Example 3. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0020] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.
[0022] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0023] The present application provides a BaF2 substrate 3.7-4.8 μm & 7.7-9.5 μm dual-band anti-reflection film, comprising a substrate layer, on which a Y2O3 layer with a thickness of 20±5 nm, a ZnSe layer with a thickness of 111±2 nm, a YbF3 layer with a thickness of 328±3 nm, a ZnSe layer with a thickness of 640±5 nm, a Ge layer with a thickness of 86±0.5 nm, a ZnSe layer with a thickness of 81±1 nm, a Ge layer with a thickness of 350±3 nm, a ZnSe layer with a thickness of 71±1 nm, a Ge layer with a thickness of 147±1.5 The anti-reflection film is relatively sensitive. Adjusting the film sequence and even the thickness will affect the performance of the film. The present application uses the MacLeod optical film design software to simulate and determine the tolerance range of each layer. During processing, the following steps are performed in sequence:
[0024] Step S1: Use the APS ion source of the physical vapor deposition coating equipment to bombard the substrate surface for 6 minutes, fill with argon gas, gas flow rate 10-12sccm, bias voltage 100-120V, discharge voltage 60-90V, discharge current 30-50A, coil current 1-3A. This step can effectively remove fine particles that are attached to the substrate during the clamping process due to static electricity or air flow disturbance during vacuuming of the coating equipment, thereby ensuring the cleanliness of the substrate;
[0025] Step S2: On the surface of the base layer, a Y2O3 layer, a ZnSe layer, a YbF3 layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, and a ZnS layer are sequentially plated. In this film structure, the Y2O3 layer is a transition connecting layer, which can improve the firmness of the film; the remaining film layer structures are arranged in a certain thickness and order, which can improve the optical properties of the film.
[0026] The plating temperature is 150-170°C, APS ion source is used for assisted deposition, the gas is argon, the gas flow rate is 8-10sccm, the bias voltage is 100-120V, the discharge voltage is 60-90V, the discharge current is 20-40A, and the coil current is 1-3A;
[0027] Step S3: Use physical vapor deposition coating equipment to maintain the deposition temperature for 1 hour after the film deposition is completed, then turn off the heat preservation, and take out the parts after naturally cooling to below 50 degrees Celsius. This can effectively release the film stress and ensure the stability of the film.
[0028] Example 1
[0029] A Φ25.4mm×3mm BaF2 material plane mirror was selected, and the surface of the substrate was bombarded for 6 minutes in the dual band range of 3.7-4.8μm & 7.7-9.5μm using an APS ion source, filled with argon, a gas flow rate of 12sccm, a bias voltage of 120V, a discharge voltage of 80V, a discharge current of 50A, a coil current of 2.5A; at 150°C, an APS ion source assisted deposition method was used, filled with argon, filled with argon, a gas flow rate of 10sccm, a bias voltage of 110V, a discharge voltage of 80V, a discharge current of 35A, and a coil current of 1.5A, and a Y2O3 layer with a thickness of 20nm, a ZnSe layer with a thickness of 110.7nm, a YbF3 layer with a thickness of 328.1nm, a ZnSe layer with a thickness of 640.2nm, and a ZnSe layer with a thickness of 8 were deposited in sequence. 5.7nm Ge layer, 81.1nm ZnSe layer, 349.8nm Ge layer, 70.7nm ZnSe layer, 146.8nm Ge layer, 89.1nm ZnSe layer, 171.5nm YbF3 layer, 75.8nm ZnSe layer, 71.5nm Ge layer, 36.1nm ZnSe layer, 585.0nm YbF3 layer, 130.0nm ZnS layer; after plating, use physical vapor deposition coating equipment, maintain the deposition temperature for 1 hour after the film deposition is completed, turn off the heat preservation, naturally cool to 46 degrees Celsius and take out the parts to obtain the BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film of the present invention.
[0030] The part was subjected to environmental and physical firmness tests. A 2cm wide tape with a peel strength of not less than 2.74N / cm was firmly adhered to the surface of the film layer. After being pulled up vertically and quickly, there was no film peeling. The part was kept at 50℃±2℃ and relative humidity of 95%~100% for 24 hours, and the film layer had no defects such as peeling, peeling, cracking, and blistering. The part was subjected to a 4.9N back and forth 50 times (25 back and forth) friction test on the surface of the film layer using an eraser head wrapped with 6 layers of absorbent cotton gauze, and there was no scratch on the film layer.
[0031] The transmittance of the 3.7-4.8 μm & 7.7-9.5 μm dual-band anti-reflection film on the BaF2 substrate was measured, and the average transmittance of the anti-reflection film was measured to be 97.41% and 97.19%.
[0032] The reflectivity of the 3.7-4.8 μm & 7.7-9.5 μm dual-band anti-reflection film on the BaF2 substrate was measured, and the average reflectivity of the anti-reflection film was measured to be 0.34% and 0.53%.
[0033] Example 2
[0034] A Φ25.4mm×3mm BaF2 material plane mirror was selected, and the substrate surface was bombarded in the dual band range of 3.7-4.8μm & 7.7-9.5μm with an APS ion source, filled with argon gas, a gas flow rate of 10sccm, a bias voltage of 120V, a discharge voltage of 80V, a discharge current of 45A, a coil current of 2.6A, and 6min. At 160 ° C, APS ion source assisted deposition was adopted, argon was filled, argon was filled, the gas flow rate was 9 sccm, the bias voltage was 115 V, the discharge voltage was 80 V, the discharge current was 40 A, and the coil current was 1.8 A. A Y2O3 layer with a thickness of 20 nm, a ZnSe layer with a thickness of 110.7 nm, a YbF3 layer with a thickness of 328.1 nm, a ZnSe layer with a thickness of 640.2 nm, a Ge layer with a thickness of 85.7 nm, a ZnSe layer with a thickness of 81.1 nm, a Ge layer with a thickness of 349.8 nm, a ZnSe layer with a thickness of 70.7 nm, and a ZnSe layer with a thickness of 146.8 nm were deposited in sequence. Ge layer, ZnSe layer with a thickness of 89.08nm, YbF3 layer with a thickness of 171.48nm, ZnSe layer with a thickness of 75.84nm, Ge layer with a thickness of 71.5nm, ZnSe layer with a thickness of 36.1nm, YbF3 layer with a thickness of 585.0nm, and ZnS layer with a thickness of 130.0nm; after plating, physical vapor deposition coating equipment is used to maintain the deposition temperature for 1 hour after the film deposition is completed, and then the heat preservation is turned off, and the parts are naturally cooled to 48 degrees Celsius to take out the parts to obtain the BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film of the present invention.
[0035] The part was subjected to environmental and physical firmness tests. A 2cm wide tape with a peel strength of not less than 2.74N / cm was firmly adhered to the surface of the film layer. After being pulled up vertically and quickly, there was no film peeling. The part was kept at 50℃±2℃ and relative humidity of 95%~100% for 24 hours, and the film layer had no defects such as peeling, peeling, cracking, and blistering. The part was subjected to a 4.9N back and forth 50 times (25 back and forth) friction test on the surface of the film layer using an eraser head wrapped with 6 layers of absorbent cotton gauze, and there was no scratch on the film layer.
[0036] The transmittance of the 3.7-4.8 μm & 7.7-9.5 μm dual-band anti-reflection film on the BaF2 substrate was measured, and the average transmittance of the anti-reflection film was measured to be 97.40% and 97.12%.
[0037] The reflectivity of the 3.7-4.8 μm & 7.7-9.5 μm dual-band anti-reflection film on the BaF2 substrate was measured, and the average reflectivity of the anti-reflection film was measured to be 0.36% and 0.57%.
[0038] Example 3
[0039] A Φ55mm BaF2 material lens and a Φ25.4mm×3mm BaF2 material plane mirror were selected, and the surface of the substrate was bombarded for 6 minutes in the dual band range of 3.7-4.8μm&7.7-9.5μm using an APS ion source, filled with argon, a gas flow rate of 10sccm, a bias voltage of 110V, a discharge voltage of 80V, a discharge current of 50A, a coil current of 2.8A; at 150°C, an APS ion source assisted deposition method was used, filled with argon, filled with argon, a gas flow rate of 10sccm, a bias voltage of 110V, a discharge voltage of 80V, a discharge current of 45A, and a coil current of 1.6A, and a Y2O3 layer with a thickness of 20nm, a ZnSe layer with a thickness of 110.7nm, a YbF3 layer with a thickness of 328.1nm, and a ZnS layer with a thickness of 640.2nm were deposited in sequence. nSe layer, Ge layer with a thickness of 85.7nm, ZnSe layer with a thickness of 81.1nm, Ge layer with a thickness of 349.8nm, ZnSe layer with a thickness of 70.7nm, Ge layer with a thickness of 146.8nm, ZnSe layer with a thickness of 89.1nm, YbF3 layer with a thickness of 171.5nm, ZnSe layer with a thickness of 75.8nm, Ge layer with a thickness of 71.5nm, ZnSe layer with a thickness of 36.1nm, YbF3 layer with a thickness of 585.0nm, and ZnS layer with a thickness of 130.0nm; after plating, physical vapor deposition coating equipment is used, and after the film deposition is completed, the deposition temperature is maintained for 1 hour, and then the heat preservation is turned off, and the parts are naturally cooled to 48 degrees Celsius to take out the parts to obtain the BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film of the present invention.
[0040] Environmental and physical firmness tests were conducted on the Φ55mm BaF2 material lens and the Φ25.4mm×3mm BaF2 material plane mirror. A 2cm wide tape with a peel strength of not less than 2.74N / cm was firmly adhered to the surface of the film layer. After being pulled up vertically and quickly, there was no film peeling. The film layer was kept at 50℃±2℃ and relative humidity of 95%~100% for 24 hours, and no defects such as peeling, peeling, cracking, and blistering were found. The parts were wrapped with 6 layers of absorbent cotton gauze eraser head, and the film surface was rubbed 4.9N back and forth 50 times (25 back and forth), and there were no scratches on the film layer.
[0041] The transmittance of the 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film on the BaF2 material plane mirror substrate was measured, and the average transmittance of the anti-reflection film was measured to be 97.47% and 97.21%.
[0042] The reflectivity of the 3.7-4.8 μm & 7.7-9.5 μm dual-band anti-reflection film on the BaF2 material plane mirror substrate was measured, and the average reflectivity of the anti-reflection film was measured to be 0.32% and 0.50%.
[0043] Comparative Example 1: The only difference from Example 1 is that the Y2O3 layer is omitted.
[0044] Comparative Example 2: The only difference from Example 2 is that step S1 is omitted.
[0045] Comparative Example 3: The only difference from Example 3 is that step S3 is omitted.
[0046] Comparative Example 4: The only difference from Example 3 is that, on the base layer, there are sequentially arranged a Y2O3 layer with a thickness of 20 nm, a ZnSe layer with a thickness of 110.7 nm, a YbF3 layer with a thickness of 328.1 nm, a ZnSe layer with a thickness of 659.4 nm, a Ge layer with a thickness of 85.7 nm, a ZnSe layer with a thickness of 83.5 nm, a Ge layer with a thickness of 349.8 nm, a ZnSe layer with a thickness of 72.8 nm, a Ge layer with a thickness of 146.8 nm, a ZnSe layer with a thickness of 91.7 nm, a YbF3 layer with a thickness of 171.5 nm, a ZnSe layer with a thickness of 78.1 nm, a Ge layer with a thickness of 71.5 nm, a ZnSe layer with a thickness of 37.2 nm, a YbF3 layer with a thickness of 585.0 nm, and a ZnS layer with a thickness of 133.9 nm.
[0047]
[0048] Among them, whether there is demoulding, defects, and scratches refers to whether the film environment and physical firmness requirements of 3.4.1 in GJB2585-1995 "General Specifications for Optical Films" are met: 1. The film is firmly adhered to the surface of the film with a 2cm wide tape with a peel strength of not less than 2.74N / cm. After being quickly pulled up vertically, there is no film peeling. 2. The film is kept at 50℃±2℃ and relative humidity of 95%~100% for 24 hours, and there are no defects such as peeling, peeling, cracks, and blistering; the coating surface has no corrosion points, stains, fading, stripes, and opaque light that exceed the spectral performance of the film specified in the drawings and relevant technical documents; in Comparative Example 2, the two dust-like through holes were observed under a 60-watt incandescent lamp with a 10x magnifying glass against a black background. 3. The film layer is subjected to a pressure of 4.9N and a rubber rubbing head wrapped with degreased cloth is rubbed back and forth 50 times (25 times) on the surface of the film layer. The film layer has no signs of damage such as scratches. The average transmittance and average reflectivity refer to the average transmittance and average reflectivity of the anti-reflection film in the dual bands of 3.7-4.8μm and 7.7-9.5μm.
[0049] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for processing a 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film on a BaF2 substrate, characterized in that: The BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film includes a substrate layer, on which a Y2O3 layer, a ZnSe layer, a YbF3 layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, and a ZnS layer are sequentially arranged; on the substrate layer, a Y2O3 layer with a thickness of 20±5nm, a ZnSe layer with a thickness of 111±2nm, a YbF3 layer with a thickness of 328±3nm, a Ge layer, a ZnSe layer, a YbF3 layer, and a ZnS layer are sequentially arranged. A ZnSe layer with a thickness of 640±5nm, a Ge layer with a thickness of 86±0.5nm, a ZnSe layer with a thickness of 81±1nm, a Ge layer with a thickness of 350±3nm, a ZnSe layer with a thickness of 71±1nm, a Ge layer with a thickness of 147±1.5nm, a ZnSe layer with a thickness of 89±1nm, a YbF3 layer with a thickness of 171±2nm, a ZnSe layer with a thickness of 76±1nm, a Ge layer with a thickness of 72±1nm, a ZnSe layer with a thickness of 36±2nm, a YbF3 layer with a thickness of 585±10nm, and a ZnS layer with a thickness of 130±3nm; The processing method includes step S2, using physical vapor deposition coating equipment and adopting APS ion source assisted deposition method to sequentially coat a Y2O3 layer, a ZnSe layer, a YbF3 layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, a ZnSe layer, a Ge layer, a ZnSe layer, a YbF3 layer, and a ZnS layer on the surface of a base layer.
2. The method for processing the BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film according to claim 1, characterized in that: In step S2, the control parameters in the APS ion source assisted deposition method are: the filling gas is argon, the gas flow rate is 8-10sccm, the bias voltage is 100-120V, the discharge voltage is 60-90V, the discharge current is 20-40A, and the coil current is 1-3A.
3. The method for processing a BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film according to claim 1, characterized in that: In step S2, the plating temperature is 150-170°C.
4. The method for processing a BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film according to claim 1, characterized in that: Before step S2, step S1 is also included, wherein step S1 is to bombard the surface of the substrate using an APS ion source of a physical vapor deposition coating device.
5. The method for processing a BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film according to claim 4, characterized in that: In step S1, the control parameters of the APS ion source bombardment are: the filling gas is argon, the gas flow rate is 10-12 sccm, the bias voltage is 100-120V, the discharge voltage is 60-90V, the discharge current is 30-50A, and the coil current is 1-3A.
6. The method for processing a BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film according to claim 4, characterized in that: In step S1, the bombardment time is 5-7 minutes.
7. The method for processing a BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film according to claim 1, characterized in that: Step S3 is included after step S2. Step S3 is to keep the temperature at the time of deposition for 1 hour after the film layer is deposited and then turn off the heat preservation.
8. The method for processing a BaF2 substrate 3.7-4.8μm & 7.7-9.5μm dual-band anti-reflection film according to claim 7, characterized in that: In step S3, the heat preservation is turned off and the parts are cooled to below 50 degrees Celsius before being taken out.
Citation Information
Patent Citations
3.7-4.8 [mu] m and 7.7-9.5 [mu] m dual-band antireflection film with BaF2 substrate
CN216209995U